On Novel Fractional Operators Involving the Multivariate Mittag–Leffler Function - Muhammad Samraiz; Ahsan Mehmood; Saima Naheed; Gauhar Rahman; Artion Kashuri; Kamsing Nonlaopon (Mathematics, 2022)
The multivariate Mittag–Leffler function is introduced and used to establish fractional calculus operators. It is shown that the fractional derivative and integral operators are bounded. Some fundamental characteristics of the new fractional operators, such as the semi-group and inverse characteristics, are studied. As special cases of these novel fractional operators, several fractional operators that are already well known in the literature are acquired. The generalized Laplace transform of these operators is evaluated. By involving the explored fractional operators, a kinetic differintegral equation is introduced, and its solution is obtained by using the Laplace transform. As a real-life problem, a growth model is developed and its graph is sketched.